2022
DOI: 10.3324/haematol.2022.281214
|View full text |Cite
|
Sign up to set email alerts
|

Molecular predictors of response to venetoclax plus hypomethylating agent in treatment-naïve acute myeloid leukemia

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 12 publications
6
36
1
Order By: Relevance
“…13 In addition, ASXL1 mutations have been shown to confer sensitivity to Ven+HMA in both AML and MDS with excess blasts, unlike the case in MPN-BP. 14,15 The prognostic impact of ASXL1 mutations in blast phase MPN differs from that in MDS and de novo AML as shown in our prior work in which the presence of RUNX1 mutations but not ASXL1 predicted inferior survival in MPN-BP. 16 In an analysis of paired chronic and blast phase samples, ASXL1 mutations were detected only during blast phase disease in 33%, 16 which might explain the discrepancy in response rates to Ven+HMA.…”
Section: Lists Characteristics Of 47mentioning
confidence: 91%
“…13 In addition, ASXL1 mutations have been shown to confer sensitivity to Ven+HMA in both AML and MDS with excess blasts, unlike the case in MPN-BP. 14,15 The prognostic impact of ASXL1 mutations in blast phase MPN differs from that in MDS and de novo AML as shown in our prior work in which the presence of RUNX1 mutations but not ASXL1 predicted inferior survival in MPN-BP. 16 In an analysis of paired chronic and blast phase samples, ASXL1 mutations were detected only during blast phase disease in 33%, 16 which might explain the discrepancy in response rates to Ven+HMA.…”
Section: Lists Characteristics Of 47mentioning
confidence: 91%
“…The current study also underscores the limited value of AML-like treatment in PEL, including that of HMA + venetoclax combination. We have previously reported the value of HMA + venetoclax in both newly diagnosed and relapsed/refractory AML [ 14 16 ]. In one of these reports involving newly diagnosed AML, [ 14 ] unlike the case in the current study, responses to HMA + venetoclax were documented in 8 (32%) of 25 TP53 -mutated AML cases, most of whom expressed monoallelic TP53 alteration.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the value of HMA + venetoclax in both newly diagnosed and relapsed/refractory AML [ 14 16 ]. In one of these reports involving newly diagnosed AML, [ 14 ] unlike the case in the current study, responses to HMA + venetoclax were documented in 8 (32%) of 25 TP53 -mutated AML cases, most of whom expressed monoallelic TP53 alteration. It is possible that the difference in response rates between the two studies might be related to their difference in TP53 allelic state.…”
Section: Discussionmentioning
confidence: 99%
“…24 ASXL1 has also been described as a potential marker for improved response to venetoclax based on non-intensive therapy in previous studies. [25][26][27][28] Moreover, in one of these studies, ASXL1 mutation was found to have a favorable impact on the achievement of CR/CRi independently of the presence of a concomitant TP53 mutation. 25 On the other hand, the diagnosis of monocytic leukemia was found to favor treatment with intensive chemotherapy compared to aza-ven in the already mentioned retrospective study (CR achievement: OR=0.08, 95% CI: 0.01-0.5).…”
Section: Intensive Versus Non-intensive Therapymentioning
confidence: 95%